The effect of water temperature on the distribution of the Eastern Cape redfin minnow, Pseudobarbus afer (Peters, 1864) - Bloy, Lesley Elizabeth (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2018)
The main objective of this MSc study was to disentangle whether temperature or the presence of non-native fish was limiting the distribution of Pseudobarbus afer (Peters, 1864) in the Blindekloof stream, Eastern Cape, South Africa. The aims were to: i) describe the thermal regime of the Blindekloof stream; ii) conduct experiments to determine the preferred and critical temperatures of P. afer and; iii) use snorkel surveys to contextualise the distribution of both native and non-native fishes in the Blindekloof stream to assess whether the downstream distribution of P. afer was likely to be influenced by temperature or by the presence of non-native, predatory fishes. To describe the thermal regime, year-long temperature data from four long term monitoring sites in the Blindekloof stream were collected using Hobo temperature loggers and analysed in order to better understand the thermal profile, the thermal variation and the rate of temperature change in the stream. The warmest temperatures were recorded in late December 2015 (absolute maximum of 29.4 °C). The coolest water temperatures were recorded in early August 2015 (absolute minimum of 9.5 °C). There is both seasonal and diel variation in temperature with mean, minimum, maximum, 7 day mean, 7 day maximum and temperature ranges differing significantly between sites. With knowledge of the thermal regime of a monitored reach of the Blindekloof stream, the thermal tolerance and preference of P. afer were investigated. The thermal tolerance of P. afer was investigated using the Critical Thermal Method (CTM) which uses non-lethal endpoints (the loss of equilibrium). At low acclimatization temperatures (11.9 ± 0.7 °C), the mean CTmax of P. afer was found to be 29.9 ± 0.7 °C, while at a higher acclimatization temperature (19.9 ± 0.1 °C), the mean CTmax was 35.1 ± 0.6°C. Custom-built thermal choice tanks were used to investigate the thermal preference of P. afer in both summer and winter. The preferred median temperatures for the summer experiments ranged from 22.4 - 29.3 °C while the winter preferred median temperatures ranged from 18.5 - 23.1 °C. The thermal tolerance of P. afer was compared to the thermal regime of the stream and the results suggest that temperature is not limiting the distribution of P. afer. Snorkel surveys were used to determine the distribution of fishes in the Blindekloof stream. Analysis of the distribution data suggests that, in the absence of non-native predatory species, native fishes have the potential to inhabit pools throughout the system right to the confluence, thus predatory fishes and not temperature was limiting P. afer distributions.
Keywords: Minnows -- South Africa -- Eastern Cape; Cyprinidae -- South Africa -- Eastern Cape; Minnows -- Effect of temperature on -- South Africa -- Eastern Cape; Minnows -- Effect of exotic animals on -- South Africa -- Eastern Cape; Introduced organisms -- South Africa -- Eastern Cape